MATHEMATICAL PREDICTION OF FORMATION OF SOLID WASTE IN ZHYTOMYR - Коцюба, І. Г. (Scientific Progress & Innovations, 2014)
Studied practical experience in dealing with solid waste (MSW) in Ukraine and the developed world. The theoretical and methodological approaches to the analysis of processes of formation of solid waste, taking into account environmental, social and economic factors. A scientific and methodological support for predicting the volumes of solid waste in the city.